2015
DOI: 10.1007/s40520-015-0503-4
|View full text |Cite
|
Sign up to set email alerts
|

VNTR polymorphisms of the IL-4 and IL-1RN genes and their relationship with frailty syndrome in Mexican community-dwelling elderly

Abstract: Inflammation is a key event that is closely associated with the pathophysiology of frailty. The relationship of genetic polymorphisms into inflammatory cytokines with frailty remains poorly understood. The aim of this study was to investigate the association between VNTR polymorphisms of the IL-4 and IL-1RN genes with the risk of frailty. We included a sample of 630 community-dwelling elderly aged 70 and older. Both IL-4 and IL-1RN VNTR polymorphisms were genotyped by the polymerase chain reaction (PCR) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…IL-4 VNTR gene polymorphisms have also been linked with immune thrombocytopenic purpura (ITP) and asthma in the current literature [50,51]. In addition, IL-4 and IL-1RN (VNTR) gene polymorphisms have together been linked to frailty syndrome and type 2 diabetes mellitus [52,53]. In our research, we found that IL-4 VNTR polymorphisms were significantly associated with nasal polyps in the Turkish population (P = 0.036).…”
Section: Discussionmentioning
confidence: 58%
“…IL-4 VNTR gene polymorphisms have also been linked with immune thrombocytopenic purpura (ITP) and asthma in the current literature [50,51]. In addition, IL-4 and IL-1RN (VNTR) gene polymorphisms have together been linked to frailty syndrome and type 2 diabetes mellitus [52,53]. In our research, we found that IL-4 VNTR polymorphisms were significantly associated with nasal polyps in the Turkish population (P = 0.036).…”
Section: Discussionmentioning
confidence: 58%
“…Their associations with alopecia areata [41], coronary artery disease [42], diabetic peripheral neuropathy [43], knee osteoarthritis [44], multiple sclerosis [45], and recurrent aphthous stomatitis [46] have been studied in the Turkish population previously. Additionally, IL-4 and IL-1RA VNTR gene polymorphisms have been found related to type 2 diabetes mellitus and frailty syndrome together [47,48]. The IL-4 coding gene is located within the cytokine gene cluster on chromosome 5q31.1, a chromosomal region identified by linkage analyses containing a susceptibility gene for SCZ [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…P1 aleli, P2 alelinden daha sık; P3 ise az sayıda popülasyonda ve en nadir alel olarak gözlenmektedir. Bu 70bp VNTR polimorfizminin genin ekspresyon seviyesini değiştirdiği ve P1 alelinin P2 aleli ile karşılaştırıldığında IL-4 ekspresyonunu artırdığı gösterilmiştir (10). Daha önce yapılan çalışmalarda IL-4geni (VNTR) polimorfizminin Graves hastalığı, subakut sklerozan panensefalit, osteoartrit, idiyopatik trombositopenik purpura vebirçok kanser türü olmak üzere çeşitli hastalıklarla ilişkisi araştırılmıştır (11)(12)(13)(14)(15)(16).…”
Section: Introductionunclassified